Eficiencia del núcleo ejecutor central y la participación de los grupos de interés en el distrito de Santa Cruz 2022 - Vásquez Flores, Christian Iván (2022)
The general objective of the research was to determine the relationship between the efficiency of the Central Executing Core (CEC) and the participation of the Interest Groups (IG) in the district of Santa Cruz 2022, where an applied type study was established, descriptive level – correlational, and non-experimental design, with a sample of 45 users of the CEC Santa Cruz; for data collection, the survey technique was used, and the questionnaire as an instrument. The study revealed that the CEC is considered very efficient (33%) because the products and supplies are always delivered in good condition; the program always motivates the development of innovative undertakings; the program always offers specialized technical assistance to GI; and that always evaluates and controls the sustainability of the project. On the other hand, the participation of the IG is qualified as medium (24%) since they indicate that the CEC has never provided a claim sheet for any discomfort presented; however, the CEC almost never came to collaborate with some unforeseen event. Likewise, it concluded that the efficiency of the CEC is significantly related to the participation of the IG, with a coefficient of 0.578, which is “mean positive”, and a bilateral significance of 0.000; Regarding the Administration of resources with a coefficient of 0.460 (mean positive) with Sig., (bilateral) 0.001; for the Organization of the project with a coefficient of 0.495 (mean positive) with Sig. (bilateral) 0.001; for Social Control with a coefficient of 0.396 (weak positive) with Sig., (bilateral) 0.007; and the Supervision of the project with a coefficient of 0.368 (weak positive) and Sig., (bilateral) 0.013.